The Estimation of Water Demand and Alternative Water Resources in Patra Jasa Building Year 2020-2025 - Nandiasa, Jantiara Eka; Moyo, Ari (NAROTAMA UNIVERSITY, Indonesia, 2020)
The development of the capital city is very rapidly this will cause water demand will continue to increase along with the rate of population growth, all fulfillment of food needs, and activity of the population closely related to the needs of water. This research aims to determine the total number of water needs required by the Patra Jasa building in the years 2020-2025 and to conserve water use and costs with the presence of alternative water sources. This study used the research method of case study approaches with the accumulation of primary data and secondary data, subsequent analysis of the availability and water needs, and replaced with alternative water sources. From the results of this study, the consumption of clean water 63838.5 m3, non-consumptive water per year 46681 M3 with details of flushing needs 36500 m3, watering 6351 m3, and cooling tower 3650 M3. The potential of source research-alternative water sources as in this is a source of rainwater that can be used to meet the daily needs of the building of 879.38 m3/day so that it can cover all the needs of non-consumptive water. FRP tank design used is FRP tank 1200 m3 with a method of rain supply that can be harvested from the roof of Patra Jasa building is 320973.7 m3/year and the average requirement is 174.9 m3/day, 5274 m3/month, 63838.5 m3/year. Annual water uses savings of 57835.71 m3/year or Rp. 725,880,160.00.